2007
DOI: 10.1097/01.pap.0000249905.63211.a1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Treatment and in Outcomes Between Idiopathic and Secondary Forms of Organizing Pneumonia

Abstract: Organizing pneumonia is a major reparative response of the lung tissue to an acute injury and is a pathological hallmark of an entity called bronchiolitis obliterans organizing pneumonia (BOOP). It can be idiopathic and called cryptogenic organizing pneumonia (COP) or be secondary to various conditions such as infections, drugs, connective tissue disorders, and radiation. Fifty-seven patients with pathologically confirmed BOOP were identified and were classified as having either COP or secondary BOOP on the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 18 publications
(19 reference statements)
4
24
0
3
Order By: Relevance
“…Studies evaluating the distribution of patients with COP and secondary OP by gender have shown no significant difference between the two groups. ( 1 , 10 , 11 ) Of the 36 patients in the present study, 26 (72.2%) were female and 10 (27.8%) were male. With regard to age, studies have shown that OP is most common in the fifth and sixth decades of life.…”
Section: Discussionmentioning
confidence: 53%
“…Studies evaluating the distribution of patients with COP and secondary OP by gender have shown no significant difference between the two groups. ( 1 , 10 , 11 ) Of the 36 patients in the present study, 26 (72.2%) were female and 10 (27.8%) were male. With regard to age, studies have shown that OP is most common in the fifth and sixth decades of life.…”
Section: Discussionmentioning
confidence: 53%
“…The dramatic improvement of pulmonary symptoms and chest CT after steroid therapy is consistent with the results previously published. In a recent publication concerning 57 patients with BOOP, Krishnamohan et al found 59% of complete resolution and 30% of partial resolution after steroid therapy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…4,41,130 Secondary OP requires treatment of the underlying condition (CTD, infection) or withdrawal of the causative drug or exposure, 41 and may require a shorter treatment if the offending agent has been withdrawn. 131…”
Section: Treatment Corticosteroid Treatmentmentioning
confidence: 99%